Sustainable Development and Application of Renewable Chemicals from Biomass and Waste - Mohamad Ibrahim, Mohamad Nasir; Vázquez, Patricia Graciela; Hussin, Mohd. Hazwan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advancements in efficient energy sources have played a pivotal role in determining the present world energy structure. Renewable biomass energy has been incorporated in industrial regulations and policies in many European countries. Based on the statistics, more than one-seventh of the total world energy consumption is generated from biomass.The renewable energies movement was prompted by two important factors: a) growing world energy consumption and b) the abundance of generated biomass residues, especially in agriculture. In the case of the first, batteries containing different metals are considered, as is the production of items for human consumption (food, clothing, home comfort, etc.). In the second case, the biomass waste from plants and animals, as byproducts of cultivating and production processes, is the main source of generated waste.